تأثير موعد وعمق الزراعة في إنبات وتميز بادرات الحمص (Cicer Arietinum L.) - سليمان، نجاح علي; أبو بكر، إدريس حسين (جامعة سرت - نقابة أعضاء هيئة التدريس, 2020)
أقيمت تجربة معملية بمعمل تقنية البحوث -بقسم المحاصيل -كلية الزراعة/ جامعة عمر المختار –البيضاء -ليبيا خلال موسم 2016/ 2017 لدراسة تأثير مواعيد (1/فبراير، منتصف فبراير، 1/مارس) وأعماق الزراعة المختلفة 2/ 4/ 6 سم. على نسبة أنبات وتميز بادرات محصول الحمص. نفذت تجربة عامليه ذات عاملين بتصميم عشوائي تام في ثلاث مكررات أظهرت النتائج. •وجود فروقاً معنوية بين مواعيد الزراعة في كل صفات الإنبات المدروسة. أعطت الزراعة المبكرة (1/ فبراير) أقل عدد أيام الشروع في الإنبات (6,33 يوم) وارتفاع في نسبة الإنبات (69.6%) ومعدل الإنبات (645). كما سجل أقل عدد أيام لتميز وظهور الورقة الأولى والثانية والثالثة كما تفوق الموعد الأول (1/ فبراير) على باقي المواعيد في تأثيره على طول الجذير والريشة والوزن الغض للبادرات. •وسجلت النتائج أيضاً اختلافات معنوية عالية بين أعماق الزراعة حيث أعطت الزراعة على عمق (2 سم) أعلى القيم مقارنة بباقي الأعماق في صفات عدد أيام الشروع في الإنبات (7.22 يوم) ونسبة الإنبات (67.8%) ومعدل الإنبات (610)، وزيادة في طول البادرة والوزن الغض (13.56 سم، 3.29 جم) على التوالي وطول الريشة والجدير (7.22، 7.78 سم). •وكانت هناك فروقاً معنوية في التفاعل بين مواعيد وأعماق الزراعة في أغلب الصفات المدروسة. حيث تفوق موعد الزراعة (1/ فبراير) مع العمق (2 سم) في صفات زمن الإنبات (6.33) وأقل عدد أيام للشروع في الإنبات ولتميز الورقة الثانية أعلى المتوسطات في الوزن الغض للبادرات وطول البادرة والريشة." The experiment was carried out at cereal technology lab, of crop science dopt, Faculty of Agricultural- University of Omer AL-Mukhtar, EL-Badia, Libya, during 2016- 2017, to study Effect of Sowing date (1st February -mid February -1st march) and seeding depth (2, 4 and 6 cm) on the germination and seedling differentiation of Chickpea plant, The experiment was laid out as factorial in randomized complete design with three replication used The results revealed that *sowing date1st February had significant differences on all studied traits except germination percent that gave the least number of days for emergence (6.33 days), highest germination percentage (69,6 %), highest, germination vigor (645), gave the lowest number of days from sowing to completely rise of the 1st -2nd,and 3rd leaves, highest root and shoot length and seedling fresh weight. *Results also indicated a significant superiority of the 2 cm depth, as compared with the other taro depths for initiation of germination and germination vigor characteristics of seedlings which gave the least number of days to emergence (7.22 days), highest germination percentage (67.8 %), germination vigor (610) highest seedling length and fresh weight (13, 56 cm and 3.29 g, respectively), and length of seedling and root length (7.22, 7.78cm) respectively. *There was significant effect for the interactions between of sowing date 1st February and the depth of (2 cm) which gave the least number of days to emergence (70.6 days), reported the lowest significant values for day to emergence (5.33 days), gave the lowest number of days from sowing to completely rise of the 2nd, leaf and also gave the highest fresh weight of seedlings stem and rootlet length."
Keywords: الهندسة الزراعية -- الإنتاج الزراعي -- خصائص التربة -- البذور الزراعية